2015
DOI: 10.1007/s00484-015-1006-x
|View full text |Cite
|
Sign up to set email alerts
|

How to estimate exposure when studying the temperature-mortality relationship? A case study of the Paris area

Abstract: Time series studies assessing the effect of temperature on mortality generally use temperatures measured by a single weather station. In the Paris region, there is a substantial measurement network, and a variety of exposure indicators created from multiple stations can be tested. The aim of this study is to test the influence of exposure indicators on the temperature-mortality relationship in the Paris region. The relationship between temperature and non-accidental mortality was assessed based on a time serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The siting of the meteorological stations used in this study may introduce some bias into the results, particularly because some of the stations are located in cities with a strong urban heat island effect (which impacts the diurnal temperature range) and/or one that has amplified over the study period (e.g., Chow et al 2012 ; Hondula et al 2012 ). We anticipate that any such bias would be small in light of other studies that have reported that temperature–mortality models using single meteorological stations perform just as well as those that incorporate multiple meteorological stations from different locations across urban areas ( Guo et al 2013 ; Schaeffer et al 2016 ). Additional research is required to understand how well airport observations correlate to actual temperatures experienced by urban residents (e.g., Bernhard et al 2015 ; Kuras et al 2015 ).…”
Section: Discussionmentioning
confidence: 95%
“…The siting of the meteorological stations used in this study may introduce some bias into the results, particularly because some of the stations are located in cities with a strong urban heat island effect (which impacts the diurnal temperature range) and/or one that has amplified over the study period (e.g., Chow et al 2012 ; Hondula et al 2012 ). We anticipate that any such bias would be small in light of other studies that have reported that temperature–mortality models using single meteorological stations perform just as well as those that incorporate multiple meteorological stations from different locations across urban areas ( Guo et al 2013 ; Schaeffer et al 2016 ). Additional research is required to understand how well airport observations correlate to actual temperatures experienced by urban residents (e.g., Bernhard et al 2015 ; Kuras et al 2015 ).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore the data collected from the HKO site should accurately reflect meteorological conditions and their variations in Hong Kong. Furthermore, use of a single monitoring station for weather variables is standard for this sort of study done in urban areas,50 and a study on the use of multiple measuring stations in a densely populated European city50 found that there was ‘no added value in taking into account data from multiple weather stations when estimating exposure in the Paris area’. Another potential limitation is that our data included some non-emergency hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies suggest that the magnitude of the temperature–mortality association is either similar 12 , 13 or larger 14 when assessed using spatially refined exposure estimates versus weather station measurements. However, these studies were conducted in relatively limited geographic areas, leaving open the question of whether their findings are specific to these locations or more broadly generalizable.…”
Section: Introductionmentioning
confidence: 99%